Pengaruh IPM, TPT, dan pendapatan per kapita terhadap kemiskinan multidimensi di Indonesia dalam perspektif ekonomi Islam (2015–2024) - Dairobbi, Ahmad; Nurlaili, Nurlaili; Fitri, Ainul (STAI Auliaurrasyidin Tembilahan, 2025)
Multidimensional poverty refers to a condition in which individuals or households are unable to meet their essential needs, encompassing the dimensions of education, health, and a decent standard of living. Islamic economics emphasizes the principles of social justice, equitable wealth distribution, and social responsibility as strategic efforts to alleviate poverty. From an Islamic perspective, poverty is not merely an economic issue but also a social and moral problem that can disrupt the balance of societal life. This study aims to examine the influence of the Human Development Index, the open unemployment rate, and per capita income on multidimensional poverty in Indonesia within the framework of Islamic economic principles. The research employs a quantitative method using the VECM approach by analyzing 34 provinces in Indonesia. The results indicate that the fixed effect model is the most appropriate model, showing that the t-test results reveal a negative and significant effect of the Human Development Index and per capita income on multidimensional poverty, while the open unemployment rate has a positive and significant effect on multidimensional poverty in Indonesia.